Riesgo crediticio y proceso de cobranzas en instituciones de educación privadas - Villacrés Armas, Clara Elizabeth (2024)
Currently, unstable behavior is perceived in the economy of Ecuador, where country risk has increased and is reflected in the country's public-private institutions. This context leads to the general objective of proposing educational credit policies in the collection process for decision making in private higher education institutions. The research is descriptive-explanatory with a qualitative approach, supported by analysis-synthesis and documentary analysis methods. Theoretically, it delves into the problems that affect credit risk in private higher education institutions, marked by the level of acquisition-indebtedness of families when deciding the continuity of their children's studies; Likewise, it delves into the educational field when considering the high percentage of student dropouts. The result was confirmed in the authors' criteria (Acuña & Chavarry, 2020; Arellano & Cubi, 2013; Barr, 2006, 2008; Barr & Crawford, 2005; Brachfeld, 2013; Ettinger & Goliet, 2000; Global Ratings, 2020; Morales & Morales, 2014; Pérez Barral et al., 2020; Pérez Barral et al., 2022) consulted, determining internal-external factors associated with the increase in credit risk in these universities, confirming the need to propose policies for the collections process and decision making.